Cold Snare Polypectomy in Patients Taking Dual Antiplatelet Therapy: A Randomized Trial of Discontinuation of Thienopyridines. Issue 10 (October 2019) - Won Ma, Dae; Kim, Joon Sung; Ji, Jeong-Seon; Kim, Byung-Wook; Choi, Hwang
Abstract : INTRODUCTION: Cold snare polypectomy (CSP) is a safe and effective method for removing polyps ⩽10 mm. The aim of this study was to compare the risk of clinically significant bleeding and thromboembolic events after CSP between stopping and continuing thienopyridines in patients taking dual antiplatelet therapy (DAPT). METHODS: The study was a single-center, noninferiority, and randomized controlled study involving patients who received colonoscopy from October 2015 to October 2016. Patients receiving DAPT with polyps ⩽10 mm were randomly assigned to either the DAPT group (patients continued DAPT) or the aspirin group (patients discontinued thienopyridines for 1 week). Primary outcome was clinically significant bleeding. Secondary outcomes included intraprocedural bleeding, nonsignificant hematochezia, and occurrence of thromboembolic events. RESULTS: Forty-two patients with 104 eligible polyps were allocated to the DAPT group, and 45 patients with 101 eligible polyps were allocated to the aspirin group. Patient demographic characteristics including size, location, shape, and pathology of the removed polyps were similar in the 2 groups. Intraprocedural bleeding and nonsignificant hematochezia rates were also similar between the 2 groups (4.8% vs 2.2%, P = 0.608; 19.0% vs 8.9%, P = 0.170). No thromboembolic event occurred in either group. Only 1 patient (2.4%) in the DAPT group showed clinically significant bleeding. No significant bleeding was found in the aspirin group. DISCUSSION: Clinically significant bleeding rate after CSP for polyps ⩽10 mm in patients continuing to take DAPT was 2.4%. Therefore, CSP is a safe method for removing small polyps even in patients taking DAPT (ClincialTrials.gov number, NCT02865824).